Overexpression of TaLBD16-4D alters plant architecture and heading date in transgenic wheat - Wang, Huifang; Han, Xiaofan; Fu, Xiaofeng; Sun, Xinling; Chen, Hailong; Wei, Xirui; Cui, Shubin; Liu, Yiguo; Guo, Weiwei; Li, Ximei; Xing, Jiewen; Zhang, Yumei (Frontiers in Plant Science, 2022)
Lateral organ boundaries domain (LBD) proteins, a class of plant-specific transcription factors with a special domain of lateral organ boundaries (LOB), play essential roles in plant growth and development. However, there is little known about their biological functions in wheat to date. Our previous study demonstrated that TaLBD16-4D is conducive to increasing lateral root number in wheat. In the present work, we further examined important agronomical traits of the aerial part of transgenic wheat overexpressing TaLBD16-4D. Interestingly, it was revealed that overexpressing TaLBD16-4D could lead to early heading and multiple alterations of plant architecture, including decreased plant height, increased flag leaf size and stem diameter, reduced spike length and tillering number, improved spike density and grain width, as well as decreased grain length. Moreover, auxin-responsive experiments demonstrated that the expression of TaLBD16-4D in wild-type (WT) wheat plants showed a significant up-regulation through 2,4-D treatment. TaLBD16-4D-overexpression lines displayed a hyposensitivity to 2,4-D treatment and reduced shoot gravitropic response. The expressions of a set of auxin-responsive genes were markedly different between WT and transgenic plants. In addition, overexpressing TaLBD16-4D affected the transcript levels of flowering-related genes (TaGI, TaCO1, TaHd1, TaVRN1, TaVRN2 and TaFT1). Collectively, our observations indicated that overexpressing TaLBD16-4D could affect aerial architecture and heading time by participating in auxin pathway.